Resisting norplant : women's struggle against coercion and violence - Akhter, Farida (Dhaka : Narigrantha Prabartana, 1995)
With reference to Bangladesh.
Includes bibliographical references.
Keywords: Women -- Crimes against -- Bangladesh; Women -- Abuse of -- Bangladesh; Violence; Aggressiveness